Improvement of scientific conceptual paradigms of market development in conditions of economic globalization - Samoilyk, Iuliia (Technology audit and production reserves, 2017)
The article is devoted to scientific and conceptual models that describe the current market conditions. Object of research is a global market environment, the conceptual gist of market, relationships in a market system. Market development in a globalizing economy is multilevel and multivector. The essence of the concept of «market» gets new content in a globalized economy. Elucidation of the new characteristics of the market needs to identify new features of national markets. The methodological approach of research is being based on dialectical approach to the formation of new market paradigms and building of the conceptual models. Deduction method is being used also in the study, which is to interchange from the general to the conceptual models of partial elements of these models. Monographic method is being used to compile scientific experience. Methods of comparison, analysis and synthesis are being used to form the authors’ models. Conceptual approaches to the interpretation of the category of «market» have been received and further developed. Treatment of this category has been improved, which, unlike existing, is signifying a system of economic relations between market actors on buying and selling market objects in a defined territory for a certain period of time provided free opportunistic pricing, limited government regulation, freedom of choice and free disposal traded under limited resources under the influence of economic globalization. Conceptual model of intersectoral scientific relations to category «market» has been built. Four basic approaches (political, administrative, marketing, logistics and approach in terms of intellectual property and business) have been used for building this model. The differences between the definition «international», «world», «global», «foreign trade» has been justified. The model of the structure of the market environment factors has been constructed.